Transient Receptor Potential Melastatin 7 Cation Channel (TRPM7) Kinase: a new player in Ang II-induced hypertension - Antunes, Tayze T (Hypertension, 2016)
Transient receptor potential melastatin 7 (TRPM7) is a bi-functional protein comprising a magnesium (Mg(2+))/cation channel and a kinase domain. We previously demonstrated that vasoactive agents regulate vascular TRPM7. Whether TRPM7 plays a role in the pathophysiology of hypertension and associated cardiovascular dysfunction is unknown. We studied TRPM7kinase-deficient mice (TRPM7Δkinase) (heterozygous for TRPM7kinase) and wildtype (WT) mice infused with Ang II (400 ng/kg/min, 4 weeks). TRPM7kinase expression was lower in heart and aorta from TRPM7Δkinase versus WT mice, effects that were further reduced by Ang II infusion. Plasma Mg(2+) was lower in TRPM7Δkinase versus WT mice in basal and stimulated conditions. Ang II increased blood pressure in both strains with exaggerated responses in TRPM7Δkinase versus WT groups (p<0.05). Acetylcholine-induced vasorelaxation was reduced in Ang II-infused TRPM7Δkinase mice, an effect associated with Akt and eNOS downregulation. Vascular VCAM-1 expression was increased in Ang II-infused TRPM7kinase-deficient mice. TRPM7 kinase targets, calpain and annexin-1, were activated by Ang II in WT but not in TRPM7Δkinase mice. Echocardiographic and histopathological analysis demonstrated cardiac hypertrophy and LV dysfunction in Ang II-treated groups. In TRPM7kinase-deficient mice, Ang II-induced cardiac functional and structural effects were amplified compared with WT counterparts. Our data demonstrate that in TRPM7Δkinase mice, Ang II-induced hypertension is exaggerated, cardiac remodelling and LV dysfunction are amplified and endothelial function is impaired. These processes are associated with hypomagnesemia, blunted TRPM7kinase expression/signaling, eNOS downregulation and pro-inflammatory vascular responses. Our findings identify TRPM7kinase as a novel player in Ang II-induced hypertension and associated vascular and target organ damage.